A novel methodology for optimum energy consumption in wireless sensor networks. Issue 1 (30th April 2021) - Abbas, Mohamed; Otayf, Nasser
Abstract : Purpose: The purpose of this paper is to minimize energy usage by maximizing network life in the creation of applications and protocols Design/methodology/approach: This paper presents a novel methodology for optimum energy consumption in wireless sensor networks. The proposed methodology introduces some protocols and logarithms that effectively contributed to reducing energy consumption in these types of networks. Findings: The results of that comparison showed the ability of those logarithms and protocols to reduce that energy but in varying proportions. It can be concluded that a significant reduction in energy consumption approximately 50% could be obtained by the proposed methodology. Originality/value: Here, a novel methodology for optimum energy consumption in wireless sensor networks has been introduced.